An unusual cause of a mediastinal mass. (3rd August 2010) - Mohammed, Abdul Rafi; Rea, Rustam; Ubhi, Chas
Abstract : Primary hyperparathyroidism (PHPT) is a disorder resulting in hypercalcaemia due to autonomous over secretion of parathyroid hormone. Mediastinal parathyroid adenoma is a rare disorder which can present with a widened mediastinum on a plain film. Its always important to check calcium level in patients who present with a mediastinal mass to rule out PHPT. Recognition of this disorder is crucial to prevent long-term sequelae. The authors report an interesting case and discuss further about it, which would be of help both to a specialist and a general physician.